Building dynamic capabilities for digital innovation: a case study of entrepreneurial firms - Carvalho, Mateus Espíndola (2021)
New technologies drive firms to develop innovations for their customers and achieve performance, innovating their business models and remaining competitive in the market in the process. And to achieve the desired ends with digital technologies, it is essential to adopt an appropriate strategy matched with capabilities to innovate in the digital context. Through a multiple case study research design, this study seeks to examine how dynamic capabilities contribute to innovative firms remaining innovative in an environment characterized by uncertainty. By examining the high-order dynamic capabilities in technology-based Small and Medium Enterprises, considering the digital context, the study contributes to the digital innovation and dynamic capabilities literature, revealing how these firms are building capabilities for digital innovation. The results indicate firms deal differently with innovation, and that dynamic capabilities contribute to these firms' remaining innovative, which also offers competitiveness in the development of digital innovations.